The Relationship Between Intolerance of Uncertainty and Employment Anxiety of Graduates During COVID-19: The Moderating Role of Career Planning - Chen, Li; Zeng, Shuyu (Frontiers in Psychology, 2021)
COVID-19, which is characterized by uncertainty, makes the employment anxiety of college graduates in the period of career change more and more intense. How to deal with this challenge is particularly important. The present study took career planning as a moderating variable to explore the the relationship between intolerance of uncertainty(IU) and employment anxiety, as well as the role of career planning. In this quantitative study, the data of 563 college graduates from different schools were collected by using the Intolerance of Uncertainty Scale-12 (IUS-12), Vocational Selection Anxiety Questionnaire of University Graduate, and Career Planning Scale. The final effective sample size was 550 (the overall recovery rate was 97.7%). The results of correlation analysis showed that there was a significant positive correlation between IU and employment anxiety, while there was a significant negative correlation between career planning and IU, as well as the relationship between career planning and employment anxiety. The results of hierarchical regression analysis showed that IU significantly positively predicted the employment anxiety of graduates, and career planning moderated the relationship between IU and employment anxiety. These findings suggested that maintaining a sense of career planning can help college graduates get through smoothly in the face of uncertainty of COVID-19.